Development and evaluation of A Self-Management WeChat Public Account for skin toxic reactions of immunotherapy patients with lung cancer - Hu, Jutao (My University, 2024)
Background: The incidence and mortality of lung cancer are increasing year by year. Skin toxicity has become a common immune-related adverse event in patients with lung cancer immunotherapy. Mobile health devices have gradually developed, and electronic products are now available on the mobile medical platform to help lung cancer patients self-manage immune-related adverse events. Objectives: The study is divided into four phases.   Phase 1: Evidence summary of skin toxicity self-management of lung cancer patients with immunotherapy and scale design and framework construction of WeChat Public Account.  Phase 2: Assess the utilization of electronic devices for anti-tumor therapy in cancer patients. Phase 3: Develop the WeChat Public Account of skin toxicity in lung cancer patients with immunotherapy.Phase 4: Evaluate the usability of the Public Account. Methods: We used the literature research method in the first phase. In the second phase, the purposive sampling method and group discussion were adopted. Then we used the brainstorming method in the third phase. In the fourth phase of the study, we used the focus group approach to conduct internal testing. A  convenience sampling method was adopted to collect data. Results: Through evidence extraction, the evidence was summarized from three aspects to form 32 best evidence. Based on this evidence, we constructed the framework and generated the preliminary image-text health education knowledge. Next, we found that the patients have self-management needs through the demand analysis and built the preliminary 3 modules and function design. Finally, we modified 6 problems through the focus group, PSSUQ data indicated that the median of usability was 4.67, information quality was 4.425, and interface quality was 4.4, which shows that the users were generally satisfied with the system as a whole. The results of the usability interviews also showed that most interviewees had a good user experience with our platform. However, the function design still needs improvement. Conclusion: This study developed a WeChat Public Account which is called “FDUSCC-Nursing” based on the evidence summaries, framework construction, and demand analysis. It has been evaluated with good clinical usability and good user experiences, and it has excellent further clinical application.
Keywords: Keywords: Mobile health, Lung cancer, Immunotherapy, Symptom management